Assessing the Effect of Different Grapevine Rootstocks as a Strategy to Maintain the Yield and Quality of Vitis vinifera L. cv. “Glera” Under a Warming Climate - Patrick Marcuzzo; Luca Masiero; Giovanni Mian; Nicola Belfiore; Alessandro Romano; Lorenzo Lovat; Federica Gaiotti (Australian Journal of Grape and Wine Research)
A two-year study was carried out to investigate the effects of eight rootstocks belonging to different crosses within Vitis genus on the performance of cv Glera grown in Northeastern Italy. Vegetative growth, yield, vine water status, and chemical parameters of berry juice were analyzed with the aim of identifying more suitable genotypes for adapting to climate change conditions. During the two experimental years, different amounts of precipitation were recorded, with warmer and drier conditions observed in 2022; consequently, the interaction effects between rootstocks and year (RxY) were significant for most of the parameters analyzed. Overall, the Vitis berlandieri × Vitis riparia genotypes (SO4, K5BB, and 420A) showed the best agronomic performance, although suffering from dry conditions in the warmer vintage. Vitis berlandieri × Vitis rupestris genotypes (1103P in particular, but also 140Ru and 110R) exhibited the best tolerance to the water stress conditions that characterized the 2022 season, maintaining acceptable yield and quality. Finally, a wide variability in responses was observed among Vitis riparia × Vitis rupestris genotypes in the investigated area; 101-14 showed a higher yield and number of clusters, while Schwarzmann was the least performing, with lower yield and lower acidity of the juice at harvest; moreover, the latter rootstock showed an anticipated budbreak, making it more susceptible to late frosts. This study revealed that Glera physiological and agronomic responses may vary greatly in response to the use of different rootstocks. Some genotypes showed the ability to confer to this variety a greater adaptability to high temperature and drought. These findings provide valuable insights for the selection of rootstocks capable of sustaining yield and preserving quality in the Glera variety under the projected climatic changes in the study area.